Measurement of the muon antineutrino double-differential cross section for quasielastic-like scattering on hydrocarbon at Eν∼3.5 GeV - Patrick, C.E.; Aliaga, L.; Bashyal, A.; Bellantoni, L.; Bercellie, A.; Betancourt, M.; Bodek, A.; Bravar, A.; Budd, H.; Caceres, G.F.R.V.; Carneiro, M.F.; Chavarria, E.; et al. (American Physical Society, 2018)
We present double-differential measurements of antineutrino charged-current quasielastic scattering in the MINERvA detector. This study improves on a previous single-differential measurement by using updated reconstruction algorithms and interaction models and provides a complete description of observed muon kinematics in the form of a double-differential cross section with respect to muon transverse and longitudinal momentum. We include in our signal definition zero-meson final states arising from multinucleon interactions and from resonant pion production followed by pion absorption in the primary nucleus. We find that model agreement is considerably improved by a model tuned to MINERvA inclusive neutrino scattering data that incorporates nuclear effects such as weak nuclear screening and two-particle, two-hole enhancements.
Keywords: Physics; Muon; Nuclear physics; Pion; Neutrino; Particle physics; Scattering; Differential (mechanical device); Lepton; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.03